Project Financing Asset-Based Financial Engineering - Finnerty, John D. (Wiley Finance Ser, 2013)
A timely update to one of the most well-received books on project financing As an effective alternative to conventional direct financing, project financing has become one of the hottest topics in corporate finance. It's being used more and more frequently-and more successfully-on a wide variety of high-profile corporate projects, and has long been used to fund large-scale natural resource projects. But the challenges of successful project financing are immense, and the requirements of the process can easily be misunderstood. That's why John Finnerty has returned with the Third Edition of Project Financing. Drawing on his vast experience in the field, Finnerty takes you through the process step by step. Using updated examples and case studies that illustrate how to apply the analytical techniques described in the book, he covers the rationale for project financing, how to prepare the financial plan, assess the risks, design the financing mix, raise the funds, and much more. Includes completely new chapters that cover the financing of sustainable projects as well as Sharia-compliant (Islamic) project financing New material has been added to the discussion of financial modeling and international debt financing Explores today's most innovative financing techniques and analyzes the shortcomings of unsuccessful project financing attempts Whether you're a corporate finance professional, project planner, or private investor, Project Financing, Third Edition demystifies the complexities of project financing and provides an invaluable guide for anyone who wants to master innovation in corporate finance today